Synthesis of Dual Program Control for a Multidimensional Dynamical System - Shepet, I. P.; Litvin, D. B. (Journal of mathematical sciences (New York, N.Y.), 2022)
In this paper, the authors consider the problem of the synthesis of dual program control for a multidimensional dynamic system and propose various quality indexes for dual program control. Based on the Rayleigh–Ritz method, they synthesize a control law for the spatial position of a sensor unit in an inertial navigation system.